Dampak Pengangguran, Pendidikan dan Inflasi Terhadap Kemiskinan di Indonesia Periode Tahun 2014-2020 - Sulasih, Sulasih; Novandari, Weni; Findianingnsih, Arisa (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Indonesia is developing countries. To become a developed country, needs to fix existing problems, especially economic problems. Economic problems are divided into 2 categories, namely micro and macro. One of the discussions in macroeconomic is related to poverty. The problem of poverty in Indonesia is an important problem to be addressed immediately because the percentage level of poverty in Indonesia is quite high and fluctuates. The rise and fall of the poverty level is related to several economic indicators, one of which is unemployment and education. In addition, poverty is also influenced by economic development indicators, including inflation. The purpose of this study is to determine the effect of unemployment, education, and inflation on poverty in Indonesia for periode 2014-2020 either partially or simultaneously. This type of research is a quantitative research because the data used is in the form of numbers. The data in this study are secondary data sourced from the Central Statistics Agency (BPS). Sampling technique using saturated sampling technique. While the data analysis in this study used multiple regression analysis because the independent variables in this study were more than 2. The results of this study indicated that the variables of unemployment and inflation have a positive and significant effect on poverty in Indonesia for the period 2014-2020. While the education variable has no effect on poverty in Indonesia for the period 2014-2020. Then simultaneously, the variables of unemployment, education, and inflation have a positive and significant effect on poverty in Indonesia for the period 2014-2020.